The impact of teacher leadership on teaching practices: the mediating role of teacher-student relationship - Ira, Akhada; Suhariadi, Fendy (Graduate School of Universitas Negeri Malang, 2024)
Leadership in an educational institution is seen more in school leadership. While on the other hand there is teacher leadership which is very urgent for its existence teaching quality. This teaching practice is an activity that is directly in contact with users of educational services, namely students. Many things related to teacher leadership have an impact on teaching practice. This study seeks to explain the influence of teacher leadership on teaching practice by using the teacher-student relationship as mediation. The quantitative method was used in this study through an electronic questionnaire filled out by 130 teachers from eight private Islamic elementary schools in the city and district of Mojokerto. Using SEM (structural equation modeling) techniques through the SMART PLS 4.0 application, we examined the data to ascertain the direct and indirect influence of teacher leadership on teaching practice. The indirect effect was observed using the teacher-student relationship as the mediating variable. The observation results show that teacher leadership has a significant direct or indirect effect on teaching practice. The mediating nature of the teacher-student relationship is partial mediation. The findings in this study show the urgency of teacher leadership in teaching practice through institutional, professional development and collaboration with fellow teachers. Furthermore, teacher-student relations which include handling conflicts and building closeness with students also play a role for quality teaching practices. This research provides additional evidence regarding the urgency of the role of teacher leadership aspects in teaching, in addition to professional, pedagogic, social and personality aspects which have been used so far in the world of education in Indonesia.